A DC–DC converter with quadratic gain and input current ripple cancelation at a selectable duty cycle. (February 2017) - García–Vite, Pedro Martín; Soriano–Rangel, Carlos Abraham; Rosas–Caro, Julio Cesar; Mancilla–David, Fernando
Abstract: This paper proposes a dc–dc converter with quadratic voltage gain able to drain ripple–free current from the source at a selectable duty cycle. Because of these features, the topology proposed herein is of special interest in renewable energy systems which have low voltage generation sources and are sensitive to current ripple from converters. The paper discusses the converter's principle of operation, focusing on modeling and design guidelines. The topology is validated through computer simulations and hardware prototyping. Highlights: Quadratic–gain converter with zero input current ripple at a selectable duty cycle. Dynamic modeling in terms of state space equations. Detailed discussion about components sizing. Validation through computer simulation and experimental prototyping.